Process techniques for engineering high-performance materials - Oberle, Tim. (Boca Raton : CRC Press, 2013)
'This book is directed toward those who conduct product development in the materials industry and engineers who convert materials into fabricated products. Real world case studies give the book a narrative, hands-on feel that appeals to readers in industry. This approach steers clear of the theory and abstraction that characterize academic works. It documents the practical mechanics of development activities to bring new and modified materials to market. It covers the methodologies for plant scale trials and field testing at customer operations'--
Includes bibliographical references and index.
Keywords: Manufacturing processes; Materials